Audit adjustments matter: What they reveal about companies' financial reporting - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2022)
This study investigates the characteristics, nature and extent of proposed audit adjustments to the financial statements of listed companies in Singapore. Data was gathered from the 2018 to 2020 financial statements of 412 companies, along with views of close to 280 audit committee chairs and heads of finance (or similar designations) on the effectiveness of their companies’ finance function.